2018
DOI: 10.1108/bfj-10-2017-0559
|View full text |Cite
|
Sign up to set email alerts
|

From informational towards transformational advertising strategies? A content analysis of Belgian food magazine advertisements

Abstract: Belgian food advertising was selected as an adequate representation of Western (European) food advertising because marketing in Belgium is permeated by international influences (cf., Belgian Federal Government). Advertisements were sampled from three magazines over a period of five years, from January 2009 to December 2013. The sample comprised 325 unique advertisements, including 159 for healthy foods and 166 for unhealthy foods. Findings: The results of the content analysis indicated that healthy food advert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Healthy food advertising is not found as effective as unhealthy food advertising (Pettigrew, 2016). As indicated before, this may be because healthy food advertising often uses a rational approach, whereas unhealthy food advertising is found to embrace a more emotional approach (Roose et al, 2018), including the use of pleasure (Pettigrew, 2016). The results of the present study indicate that pleasure may be equally promising in the promotion of healthy food.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthy food advertising is not found as effective as unhealthy food advertising (Pettigrew, 2016). As indicated before, this may be because healthy food advertising often uses a rational approach, whereas unhealthy food advertising is found to embrace a more emotional approach (Roose et al, 2018), including the use of pleasure (Pettigrew, 2016). The results of the present study indicate that pleasure may be equally promising in the promotion of healthy food.…”
Section: Discussionmentioning
confidence: 99%
“…However, because pleasure is an important factor driving human behavior, it is considered equally interesting in the promotion of healthy eating. Contemporary healthy food campaigns take on a more rational perspective by providing information and relying on knowledge (Guthrie, Mancino, & Lin, 2015; Pérez‐Cueto, Aschemann‐Witzel, Shankar, & Verbeke, 2011; Roose, Geuens, & Vermeir, 2018). Although this perspective has been proven successful in creating awareness of the importance of a healthy diet (Pérez‐Cueto et al, 2011), the effect on actual lifestyle changes is questioned (Bucher et al, 2016; Just & Payne, 2009; Pérez‐Cueto et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…At first sight, the findings by Elder and Krishna [17] could suggest that multiple-sense ads can also promote healthy food. However, previous research shows that healthy food advertising and unhealthy food advertising often use different advertising techniques [33] and also call for different advertising techniques in order to be effective [34].…”
Section: Sensory Advertising For Healthy Versus Unhealthy Foodmentioning
confidence: 99%
“…No research to date has investigated what the effects of a specific picture–word ratio is on product perceptions, attitudes and behaviour. Research of Roose et al [ 281 ] seems to suggest that visual cues in particular should be used to attract low involvement customers. Via a content analysis of food advertising, the authors found that informational cues (i.e., mostly verbal cues) are mostly prevalent in healthy food advertising while, transformational cues (i.e., mostly visual cues) dominate unhealthy food advertising.…”
Section: Object Processed Cuesmentioning
confidence: 99%
“…People looked longer at the text than the cartoon and the cartoon was not given full inspection until the text had been read. Also, Hegarty [ 281 ] shows that the comprehension process is largely text directed. Similarly, Rayner et al [ 278 ] found that viewers tended to read the large print, then the smaller print, and then they looked at the picture.…”
Section: Object Processed Cuesmentioning
confidence: 99%